Light as a visual source domain for the divine in the 17th century painting - Čulig Suknaić, Janja (Array, 2019)
The aim of this paper is to explain the motivation behind the creation of religious visual art in which light plays the role of the signifier of divine presence. We will endeavor to show that representations of light in paintings from a particular socio-cultural period and context are based on metaphorization. The meaning that arises from this metaphorization establishes a connection between depicted light and the basic conceptual metaphor KNOWING IS SEEING. Our aim is to show that the understanding of these kinds of representations by the viewer as the presence of the divine is based on the fundamental human capacity to conceptualize abstract notions through concrete ones. We propose that a visual representation of light would not be completely understandable if the viewer did not possess an inherent knowledge of basic conceptual metaphors of light. The visual material selected for this article comprises samples of 17th century religious paintings of the Western artistic tradition, in which light serves as the primary carrier of divine meaning and the central element of the composition. Our proposition is based on the conjoining of two disciplines into an interdisciplinary approach to analyzing paintings from the Baroque period. The selected theoretical framework includes Conceptual Metaphor Theory and the conceptualization of abstract notions (Lakoff & Johnson 1980; Gibbs 1994, 2008; Kövecses 2005; Forceville & Urios-Aparisi 2009; Sharifian 2011; Raffaelli 2012; Forceville 2017), as well as art-historical insights into the utilization of pictorial elements of light in the formal visual language of the Baroque (Haskell 1963; Lambert 2007; Toman 2007; Cvetnić 2007). The significance of this kind of research lies in the prospects of interdisciplinary approaches to concepts in general.